ANALISIS KANDUNGAN ASAM ASKORBAT PADA TANAMAN KANGKUNG (Ipomoea reptana Poir), BAYAM (Amaranthus spinosus), dan KETIMUN (Cucumis sativus L) - Andi Nugroho, Setyo (Jurnal TAMBORA, 2020)
Plants have a defense mechanism against increasing oxidative compounds formed due to drought stress. One of the compounds forming these compounds is ascorbic acid. Ascorbate is the main metabolite compound in plants that has an antioxidant function, which protects plants from oxidative damage resulting from aerobic metabolism. The aim of the study was to standardize and analyze the content of Ascorbate (ASA) on the leaves of kale (Ipomoea reptana Poir), spinach (Amaranthus spinosus) and cucumber (Cucumis sativus, L). The method used was 0.5 g leaf samples were crushed with 5% metaphosphoric acid. The solution obtained was titrated with dichlorophenol-indophenol (DCIP) 0.8 g / l. Treatment analysis of ascorbic acid (ASA) content in this plant tissue which has the largest ascorbic acid content in cucumber plants (Cucumis sativus L) of 69855.85; then followed by spinach plants (Ipomoea reptana Poir) at 66517.24 and finally in spinach (Amaranthus spinosus) at 38859.13. And the ASA mg standard 308.